2016
DOI: 10.12816/0033272
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Influencing the Project Success : An Analysis of Projects in Manufacturing and Construction in Pakistan

Abstract: Effective and efficient management of critical success factors is the basic requirement of project success. Many researches have been conducted on the Critical Factors influencing the Project Success but very few studies have been conducted in construction and manufacturing industries in Punjab. Therefore, the existing study aims also analysis of critical success factors influencing the project success in Punjab. To collect the data for the purpose of this study, the sample from which data was collected was 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 7 publications
1
24
0
1
Order By: Relevance
“…Some researchers consider it positive and supportive because knowledge workers create a pressure group for the social welfare of the employees. However, previous studies have found that POP affects organizational performance, creates bottlenecks in achieving organizational goals and creates pressure groups to halt developmental and progressive organizational activities (Hassan et al, 2017;Iram et al, 2016).…”
Section: Literature Review 21 Perceived Organizational Politics (Pop)mentioning
confidence: 99%
See 4 more Smart Citations
“…Some researchers consider it positive and supportive because knowledge workers create a pressure group for the social welfare of the employees. However, previous studies have found that POP affects organizational performance, creates bottlenecks in achieving organizational goals and creates pressure groups to halt developmental and progressive organizational activities (Hassan et al, 2017;Iram et al, 2016).…”
Section: Literature Review 21 Perceived Organizational Politics (Pop)mentioning
confidence: 99%
“…When capital becomes negative, ruin occurs (Alon and Martin, 1998;Florio and Leoni, 2017). Therefore, probability calculation is mandatory for management as it indicates the soundness of the combined premiums and the claim process (Iram et al, 2016). In projects, at the time of initial investment, the probability of ruin remains high, indicating instability that demands more premiums/investment and working capital.…”
Section: Theoretical Perspectivementioning
confidence: 99%
See 3 more Smart Citations